Extracellular vesicles: messengers of cross-talk between gastric cancer cells and the tumor microenvironment - Li, Xiwen; Lu, Xian; Liu, Mi; Chen, Junjie; Lu, Xirong (Frontiers in Cell and Developmental Biology, 2025)
Gastric cancer is a common malignancy characterized by an insidious onset and high mortality rate. Exosomes, a special type of extracellular vesicle, contain various bioactive molecules and have been found to play crucial roles in maintaining normal physiological functions and homeostasis in the body. Recent research has shown that the contents of exosome play a significant role in the progression and metastasis of gastric cancer through communication and regulatory functions. These mechanisms involve promoting gastric cancer cell proliferation and drug resistance. Additionally, other cells in the gastric cancer microenvironment can regulate the progression of gastric cancer through exosomes. These include exosomes derived from fibroblasts and immune cells, which modulate gastric cancer cells. Therefore, in this review, we provide a brief overview of recent advances in the contents and occurrence mechanisms of exosome. This review specifically focused on the regulatory mechanisms of exosomes derived from gastric cancer and other cellular subtypes in the tumor microenvironment. Subsequently, we summarize the latest research progress on the use of exosomes in liquid biopsy, discussing the potential of gastric cancer exosomes in clinical applications.